Word Length Selection Method for Controller Implementation on FPGAs Using the VHDL-2008 Fixed-Point and Floating-Point Packages. (11th August 2010) - Urriza, I.; Barragán, L. A.; Navarro, D.; Artigas, J. I.; Lucia, O.
Abstract : This paper presents a word length selection method for the implementation of digital controllers in both fixed-point and floating-point hardware on FPGAs. This method uses the new types defined in the VHDL-2008 fixed-point and floating-point packages. These packages allow customizing the word length of fixed and floating point representations and shorten the design cycle simplifying the design of arithmetic operations. The method performs bit-true simulations in order to determine the word length to represent the constant coefficients and the internal signals of the digital controller while maintaining the control system specifications. A mixed-signal simulation tool is used to simulate the closed loop system as a whole in order to analyze the impact of the quantization effects and loop delays on the control system performance. The method is applied to implement a digital controller for a switching power converter. The digital circuit is implemented on an FPGA, and the simulations are experimentally verified.